2005
DOI: 10.1038/sj.bmt.1705046
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD25 monoclonal antibody (basiliximab) for prevention of graft-versus-host disease after haploidentical bone marrow transplantation for hematological malignancies

Abstract: Summary:Haploidentical donors are available for most patients who need allografts but do not have matched donors. However, GVHD, rejection, delayed immune reconstitution, and infections have been significant barriers. We designed a haploidentical BMT protocol focusing on prevention of GVHD and rejection. A total of 53 leukemic patients underwent haploidentical G-CSF-primed BMT without ex vivo T-cell depletion. GVHD prophylaxis consisted of antithymocyte globulin, cyclosporine, methotrexate, and mycophenolate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…A significant reduction in the incidence of grade II-IV aGVHD from 33 to 11% was recorded in our center when adding basliximab to CsA, MTX and MMF after haploidentical HSCT for hematological malignancies. 22 Another study from Fang et al 23 indicated that basliximab prevents GVHD efficiently following unrelated PBSCT. The incidence of grade III-IV aGVHD and cGVHD was 15.9 and 38.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in the incidence of grade II-IV aGVHD from 33 to 11% was recorded in our center when adding basliximab to CsA, MTX and MMF after haploidentical HSCT for hematological malignancies. 22 Another study from Fang et al 23 indicated that basliximab prevents GVHD efficiently following unrelated PBSCT. The incidence of grade III-IV aGVHD and cGVHD was 15.9 and 38.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72] First, over the years in the HLA matched setting, the addition of broadly active immunosuppressants or lymphocyte depletion has yet to limit the GVHD problem compared with standard calcineurininhibitor/MTX prophylaxis, without the consequence of higher relapse/progression rates. Second, patients referred to our institution for NMAT were of advanced age or with comorbid conditions and intermediate to poor cytogenetics, but not in florid relapse; therefore, a potent, welltolerated therapy for older recipients with high-risk features and low tumor burden is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Two kinds of recipient mice, (B6 Â bm1) F 1 or (B6 Â bm12) F 1 , were used to develop CD8T-celldependent acute GVHD (CD8-GVHD) or CD4T-celldependent acute GVHD (CD4-GVHD), respectively. 5,6 CD4 or CD8T cells were prepared from B6 splenocytes with anti-CD4-or anti-CD8-conjugated magnetic beads, respectively. Each type of acute GVHD was induced by adaptive transfer of CD8 or CD4T cells to irradiated recipient mice.…”
Section: Suppressive Effect Of Nk026680 On Allogeneic T-cell Responsesmentioning
confidence: 99%
“…[1][2][3] Then, allogeneic donor T cells primarily recognize major histocompatibility complex (MHC) antigens on host DCs, and subsequently activate and proliferate in the presence of DC-derived accessory signals and cytokines. Currently proposed or practiced prophylaxis for acute GVHD includes use of a monoclonal antibody to CD52, 4 CD25, 5,6 cytotoxic T-lymphocyte antigen-4 7 or tumor necrosis factor-alpha (TNFa) 8 all of which are DC-specific antigens and/or take part in T-cell activation in the antigen presentation stage. Currently increasing studies for the development of immunosuppressive drugs have been evaluating DC function as a pharmacological target for prevention of acute GVHD.…”
Section: Introductionmentioning
confidence: 99%